Trichoderma harzianum-loaded maize biochar enhances Cd–Cu immobilization and reduces bio-accessibility in contaminated soil - Asif Kamal; Moona Nazish; Khalid Kamal; Mahnoor Akbar; Faseeha Ansir; Nawaira Aslam; Muhammad Sohail Riaz; Gadah Albasher; Muhammad Farooq Hussain Munis (Scientific Reports)
Abstract The use of microbial loaded biochar in soil remediation is becoming popular worldwide. In the current research, a maize straw biochar (MB) and Trichoderma harzianum loaded biochar (MBT) were used at various rates in Cd–Cu dual polluted soil, to see their effect on Cd–Cu removal and to explore vigorous changes of metals bio-accessibility. Throughout the 90 days of remediation experiment, the dynamic impacts on the soil’s physiochemical characteristics were noted. According to the current study’s findings, applying 5% MBT to the soil early in the incubation period significantly raised its pH, which eventually dropped to a neutral-alkaline level. The application of MBT promoted residual bound Cu–Cd fraction and decreased carbonate and exchangeable bound fraction in the treated soil. The exchangeable portion of Cd highly decreased by 15.33% in the MBT5 amendments. Similarly, the DTPA extractable Cu and Cd concentration (i.e., DTPA-Cu, DTPA-Cd) in the amended soil gradually decreased with time. After 90 days, the DTPA-Cd contents lowered from 45 mg kg− 1 in CT to 25.3 mg kg− 1 in MBT5 whereas the DTPA-Cu concentration was 62.3 mg kg− 1 in MBT5, respectively. The Cd bio-accessibility of gastric juice was reduced in all treatments including 68.1% of MBT5. Gastrointestinal fractions at the various treatments were recorded to be 73% (MB1), 71.1% (MBT1), 67.4% (MB5), and 63.5% (MBT5). In comparison, an obvious reduction in Cu bio-accessibility was perceived in all four amendments, viz. MB1 (72.5%), MBT1 (69.6%), MB5 (65.1%), and MB5 (61.4%) in gastric solution. The addition of MBT also enhanced soil enzymatic activity particularly urease and catalase, in the later phase of the experiment, showing the retrieval function of soil for the post-stabilization of metal. The present study confirmed that MBT effectively reduces Cd and Cu bio-accessibility and mobility, supporting long term soil stabilization. It also restores soil enzymatic activity, making it a sustainable and ecofriendly approach for heavy metal remediation.